ANALYSIS OF PARTICIPATION OF MELABUN PERMAI GAPOKTAN MEMBERS TO FOLLOW THE PEOPLE'S OIL PALM REJUVENATION (PSR) PROGRAM IN BANGKA CENTRAL DISTRICT - Demsi Apriadi; Eries Dyah Mustikarini; Fournita Agustina; Evahelda (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The People's Oil Palm Rejuvenation Program (PSR) is a National Strategic Program as an effort by the Government to increase the productivity of oil palm plantations. One important factor that determines the success of replanting activities is the participation of farmers, where without the participation of farmers, rejuvenation activities will not be successful, due to the role of farmers as the main actors in agricultural development programs. The purpose of this study was to determine the level of farmer participation and the factors that are significantly related to the implementation of People's Oil Palm Rejuvenation (PSR) in Sungaiselan District, Central Bangka Regency. The study of Gapoktan Melabun Permai in Sungaiselan Subdistrict, Central Bangka Regency was carried out from May to June 2023. The sample in this study was Gapoktan Melabun Permai, Sungaiselan District in Central Bangka Regency, totaling 59, the sampling technique of this study was non-probability sampling using consecutive sampling method, data collection used a questionnaire that had been tested for validity and reliability. Methods of data analysis to determine the participation of Gapoktan Melabun Permai in PSR using multiple linear regression analysis. The results of the study found that the participation of Gapoktan Melabun Permai in the implementation of the People's Palm Oil Rejuvenation (PSR) program in Sungaiselan District, Central Bangka Regency, was in the very high category with a percentage of 91.58%. After conducting multiple linear regression analysis, there is a significant relationship between the factors of land area, motivation,